Evaluation of Academic Supervision of Catholic School Principals in Improving Teacher Professionalism - Warman Warman (PT ARRUS Intelektual Indonesia, 2022)
This study aims to describe the evaluation and follow-up program of the results of the principal's academic supervision in increasing teacher professionalism at a Catholic school in Samarinda City. This research uses a qualitative approach with the type of case study research. Data collection in the study involved three informants, namely the principal, the vice principal of the curriculum, and the teachers. Data collection methods used are observation, interviews, and documentation. The process of data analysis is carried out through the stages of reduction, presentation, and drawing conclusions. The results of this study indicate that the evaluation and follow-up of the results of supervision is a very strategic activity regarding efforts to increase teacher professionalism so that it has an impact on improving the quality of the process and student learning outcomes. In the evaluation stage, the principal analyzes the results of class visits related to the learning process which consists of lesson planning and learning implementation. The evaluation process is first carried out by the principal and teachers individually, then in groups in the form of an evaluation meeting. This emphasizes the final outcome in a collective agreement. Based on the results of the evaluation, the follow-up program given by the principal to teachers to develop their professionalism is to provide specific direction and guidance, participate in technical guidance, hold workshops, participate in teacher consultation forums, attend seminars, recommend further studies, and hold a library. especially for teachers. This is expected to provide various teaching skills with various models and teaching methods for teachers in improving the quality of learning in schools.